Frederick C. Ainsworth papers - Ainsworth, Fred C. (Fred Crayton), 1852-1934.
Letters relating mainly to smokeless powder, investigations of rifle bore corrosion, and a new or improved composition for the cleaning and lubricating of gun and rifle barrels. Correspondents include Edward C. Crossman and Arno Carl Fieldner.
Army officer.
Collection material in English.
Keywords: Crossman, Edward C. -- 1881-; Fieldner, Arno Carl, -- 1881-1966.; United States. -- Army -- Ordnance and ordnance stores; Ammunition; Firearms; Ordnance; Army officers